Zavedení managementu bezpečnosti ICT na střední škole - Matusík, Jan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Obsahem této bakalářské práce je návrh zavedení managementu bezpečnosti ICT na konkrétní střední škole v Moravskoslezském kraji. Úvodní část popisuje objekt školy a dosavadní management bezpečnosti. V praktické části této práce jsou poté rozebrány nedostatky. Především z hlediska používaných bezpečnostních mechanismů, chování uživatelů, správců. Součástí práce jsou také návrhy na řešení dané situace.

The aim of this bachelor’s thesis is proposal of implementation of the ICT Security Management to the specific Highschool in the Moravian-Silesian region. Introduction part describes the school building and current Security Management. In the practical part of this thesis are then discussed the shortages in the Highschool. This is done mainly from the perspective of security mechanisms used and the behavior of users and administrators. There are also proposals how to deal with this situation in this work.
Implementation of ICT Security Management in Highschool
Keywords: Management bezpečnosti; bezpečnost; ICT; ISO/IEC 27000; Security management; security; ICT; ISO/IEC 27000